2020
DOI: 10.35229/jaes.824177
|View full text |Cite
|
Sign up to set email alerts
|

Ankara Asartepe Baraj Gölü’nde Yaşayan Oxynoemachellus angorae (Steindachner, 1897)’ nın Boy-Ağırlık ilişkileri ve Kondisyon Faktörü

Abstract: Öz: Asartepe Baraj Gölü'nde M art 2015-Şubat 2016 tarihleri arasında yürütülen bu çalışmada Oxynoemacheilus angorae (Steindachner, 1897)'nın boy -ağırlık ilişkileri (LWR), kondisyon faktörü ve boy-boy ilişkileri araştırılmıştır. Elde edilen örneklerin total boyları 4-7,8 cm, toplam ağırlıkları ise 1-5 g arasında dağılım göstermiştir. Boy -ağırlık ilişkisinin fonksiyonel denklemi W = 0,00171×TL 2,651 ve korelasyon değeri r 2 = 0,80 olarak hesaplanmıştır. Elde edilen b değeri tüm bireylerde istatistiksel olarak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Among them is the Angora loach, Oxynoemacheilus angorae (Steindachner, 1897), which inhabits drainage basins, streams, and muddy lakes, feeding on benthic invertebrates and spawn (Froese & Pauly 2020). The Angora loach is terra typica in Ankara (Saylar et al 2020), having been reported in Marmara, Susurluk, Sakarya, and Kızılırmak basins (Özkan et al 2009; Çoban et al 2013; Yıldırım et al 2015; Sağlam et al 2017). Furthermore, this species is also found in Israel, Jordan, Lebanon, and Syria.…”
Section: Introductionmentioning
confidence: 99%
“…Among them is the Angora loach, Oxynoemacheilus angorae (Steindachner, 1897), which inhabits drainage basins, streams, and muddy lakes, feeding on benthic invertebrates and spawn (Froese & Pauly 2020). The Angora loach is terra typica in Ankara (Saylar et al 2020), having been reported in Marmara, Susurluk, Sakarya, and Kızılırmak basins (Özkan et al 2009; Çoban et al 2013; Yıldırım et al 2015; Sağlam et al 2017). Furthermore, this species is also found in Israel, Jordan, Lebanon, and Syria.…”
Section: Introductionmentioning
confidence: 99%
“…Angora loach, Oxynoemacheilus angorae (Steindachner, 1897) inhabits different habitats such as drainage basin, streams and muddy lakes in Iran, Israel, Jordan, Lebanon, Syria, and Turkey (Froese and Pauly, 2020). Its terra typica is Ankara (Turkey) (Saylar et al, 2020). The conservation status of O. angorae was classified as Least Concern (LC) according to the IUCN Red List Criteria (Freyhof, 2014).…”
Section: Introductionmentioning
confidence: 99%